Subfossil chironomids (Diptera, Chironomidae) of lakes in the Tatra Mountains: an illustrated guide - Chamutiová, Tímea; Hamerlík, Ladislav; Bitušík, Peter (Zootaxa, 2020)
Here we present a summary of subfossil chironomids (Diptera: Chironomidae) found in the surface sediments of 52 Tatra Mts. lakes (Slovakia, Poland). Head capsules of 73 morphotypes of 5 subfamilies are described and illustrated. In addition to the previously documented subfossils by Brooks et al. (2007), we present 15 new morphotypes: Diamesa Tatra-type A, Diamesa Tatra-type B, Pseudodiamesa branickii-type, Pseudodiamesa nivosa-type, Pseudokiefferiella parva, Brillia bifida-type, Cricotopus (Paratrichocladius) skirwithensis-type, Cricotopus (Cricotopus) tremulus-type, Cricotopus/Orthocladius I, Eukiefferiella brevicalcar-type, Eukiefferiella claripennis-type B, Orthocladius (Orthocladius) dentifer-type, O. (Mesorthocladius) frigidus, Orthocladius (Euorthocladius) sp. and Tanytarsini indet. Most of these types have possibly broad distribution patterns in Europe. We believe that due to specific features of each region, this paper will serve as a helpful manual for limnologists and paleolimnologists working not only in the Tatra Mts. but also in the whole Carpathian region.